Improved selection criteria for H ii regions, based on IRAS sources. Issue 3 (3rd March 2018) - Yan, Qing-Zeng; Xu, Ye; Walsh, A J; Macquart, J P; MacLeod, G C; Zhang, Bo; Hancock, P J; Chen, Xi; Tang, Zheng-Hong
Abstract: We present new criteria for selecting H ii regions from the Infrared Astronomical Satellite ( IRAS ) Point Source Catalogue (PSC), based on an H ii region catalogue derived manually from the all-sky Wide-field Infrared Survey Explorer ( WISE ). The criteria are used to augment the number of H ii region candidates in the Milky Way. The criteria are defined by the linear decision boundary of two samples: IRAS point sources associated with known H ii regions, which serve as the H ii region sample, and IRAS point sources at high Galactic latitudes, which serve as the non-H ii region sample. A machine learning classifier, specifically a support vector machine, is used to determine the decision boundary. We investigate all combinations of four IRAS bands and suggest that the optimal criterion is $log\left(F_{60}/F_{12}\right)\geqq \left( -0.19 × log\left(F_{100}/F_{25}\right)+ 1.52\right)$, with detections at 60 and 100 ${μ}$ m. This selects 3041 H ii region candidates from the IRAS PSC. We find that IRAS H ii region candidates show evidence of evolution on the two-colour diagram. Merging the WISE H ii catalogue with IRAS H ii region candidates, we estimate a lower limit of approximately 10 200 for the number of H ii regions in the Milky Way.